2018
DOI: 10.1055/s-0037-1610274
|View full text |Cite
|
Sign up to set email alerts
|

A General Protocol for the Synthesis of H-α-Hydroxyphosphinates

Abstract: A general synthetic procedure was developed for H-α-hydroxyphosphinates via Abramov reaction. The present work is a complementary study to those reported till now. This methodology has the advantage that it can be applied to various aliphatic and (hetero)aromatic substrates. The H-α-hydroxyphosphinates were easily purified and obtained in good to excellent yields in shorter times. A 31P NMR spectroscopy study has shown that only 2 equivalents of a silylating agent were required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Then, a methanolysis step followed by a pH adjustment to 7 yielded 6a as disodium salt in an excellent yield of 91% after easy purification by precipitation. For the latter step, the preparation of bis(trimethylsilyl)phosphonite 5 can be smoothly achieved by the silylation of hypophosphorous acid in the presence of N,O-bis(trimethylsilyl)acetamide (BSA) as previously reported [12][13][14]21,24].…”
Section: Resultsmentioning
confidence: 99%
“…Then, a methanolysis step followed by a pH adjustment to 7 yielded 6a as disodium salt in an excellent yield of 91% after easy purification by precipitation. For the latter step, the preparation of bis(trimethylsilyl)phosphonite 5 can be smoothly achieved by the silylation of hypophosphorous acid in the presence of N,O-bis(trimethylsilyl)acetamide (BSA) as previously reported [12][13][14]21,24].…”
Section: Resultsmentioning
confidence: 99%
“…First, we have demonstrated that only two equivalents of BSA were required to fully transform H 3 PO 2 into BTSP, despite large excesses of silylated agents being previously employed in the literature [6]. Then, the subsequent addition on aldehydes and ketones provided various α-hydroxyphosphinates as sodium salts in good to excellent yields [7]. Aldehydes, ketones and imines can also undergo nucleophilic attack from silyla phosphonites via the Abramov reaction to give various α-hydroxy-and aminophosphinates, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…First, we h demonstrated that only two equivalents of BSA were required to fully transform H3P into BTSP, despite large excesses of silylated agents being previously employed in literature [6]. Then, the subsequent addition on aldehydes and ketones provided vari α-hydroxyphosphinates as sodium salts in good to excellent yields [7].…”
Section: Introductionmentioning
confidence: 96%
“…1 In addition, P-chiral H-phosphinates can also act as important HASPOs for homogeneous catalysis. 2 A plethora of synthetic strategies have been developed for H-phosphinates, such as the alcoholysis of aryl bischlorophosphines, 3 nucleophilic substitution of chlorophosphites, 4 palladiumcatalyzed arylation of hypophosphorous acids, 5 NiCl 2 -catalyzed hydrophosphinylation of alkynes, 6 Abramov reaction between carbonyl compounds and hypophosphorous acid, 7 and MWassisted esterification of H-phosphinic acids. 8 Particularly, Petnehaźy optimized the more benign method originally developed by Sander 9 and prepared five H-phosphinates from the relatively low-cost and easy-to-handle reagent of triethylphosphite (EtO) 3 P. 10 Subsequently, Volle conducted further investigations into the procedure, particularly with regard to the influence of the reactant concentrations and successfully prepared ten pure H-phosphinate compounds after distillation, but in only 39−63% yields (Scheme 1a).…”
Section: ■ Introductionmentioning
confidence: 99%